Sexual (Dys)function after Urethroplasty - Luís Xambre (Advances in Urology)
There is a paucity of published literature on the andrological consequences of urethral repair. Until recently authors have focused mainly on technical aspects and objective results. Reported outcomes of urethral reconstruction surgery have traditionally focused only on urodynamic parameters such as flow rates. Patient reported outcome measures have largely been neglected and there is a scarcity of well conducted systematic studies on the subject. For these reasons whether the different components of sexual life are more or less affected by different types of urethral reconstruction remains largely unknown. In an attempt to clarify the available scientific evidence, the authors make a critical review of available literature, systematizing it by sexual domain and study type. Brief pathophysiological correlations are discussed.